Insecticidal properties of a highly potent wax isolated from Dolichandra cynanchoides Cham - Diaz Napal, Georgina Natalia (2016)
Bioassay-guided fractionation of an ethanolic extract of the aerial parts of Dolichandra cynanchoides Cham. (Bignoniaceae) led to the isolation of a natural wax with anti-insect activity against Spodoptera frugiperda (Noctuidae) and Epilachna paenulata (Coleptera). The compound was identified spectroscopically as an ester of a C27 fatty acid and a C25 alcohol, pentacosyl heptacosanoate (1). The effective doses of 1 for 50% feeding inhibition (ED50) of S. frugiperda and E. paenulata were 0.82 and 8.53 μg/cm2, respectively, in a choice test, while azadirachtin showed ED50 of 0.10 and 0.59 μg/cm2, respectively. In a no-choice test, both insects refused to feed on leaves treated with 1 at doses of 0.1 μg/cm2 or greater inhibiting larval growth and dramatically reducing survival. The lethal doses 50 (LD50) of 1 were 0.39 and 0.68 μg/cm2 for S. frugiperda and E. paenulata, respectively. These results indicate that 1 has potential for development as botanical insecticides. Similar esters might be obtainable in large quantities as many edible crops produce wax esters that are discarded during food processing. Research on these materials could lead to the detection of similar waxes with insecticidal activity.